Homologous Escherichia coli Identified in Cerebrospinal Fluid and Bloodstream - Shi, Qingmiao; Zhang, Jun; Wang, Jinghui; Du, Lijuan; Shi, Zhaoyang; Xu, Min; Luo, Yonggang (Frontiers in Cellular and Infection Microbiology, 2021)
Background Escherichia coli is an opportunistic bacterium that causes a wide range of diseases, such as bloodstream infection and central nervous system infection. The traditional culture-based method to detect E. coli usually takes more than 2 days. The object of this study is to explore the value of metagenomic next-generation sequencing (mNGS) in identifying E. coli from human cerebrospinal fluid. In addition, we investigated the infection source of E. coli through whole genome sequencing and phylogenetic analysis. Methods We combined a clinical example to analyze the function of mNGS in pathogen detection from cerebrospinal fluid. NextSeq 550Dx platform was applied for mNGS. Next, whole genome sequencing was performed to obtain the genomic characterization of E. coli. Furthermore, we screened 20 E. coli strains from the National Center for Biotechnology Information and conducted a phylogenetic analysis. Results A middle-aged patient who attended our hospital was diagnosed with craniopharyngioma and received surgery. The patient had recurrent fever and persistent lethargy after surgery. Cerebrospinal fluid culture firstly failed to grow the bacteria. Next the cerebrospinal fluid sample was detected by mNGS and the sequence readings of E. coli were identified. Later, E. coli was reported via the second cerebrospinal fluid culture, certifying the result of mNGS. Moreover, we also cultured carbapenem-resistant E. coli from the patient’s bloodstream. Through whole genome sequencing and phylogenetic analysis, we found that the E. coli isolated from cerebrospinal fluid and the bloodstream was 100% homologous, indicating the E. coli central nervous system infection was originated from the bloodstream. Conclusion Metagenomic next-generation sequencing is a valuable tool to identify the pathogens from cerebrospinal fluid, and seeking the infection source is of great significance in clinical diagnosis and treatment. Furthermore, carbapenem-resistant E. coli is a serious problem as the cause of bloodstream infection and central nervous system infection, and effective and adequate measures to prevent and control the present circumstance are urgent.